2013
DOI: 10.1371/journal.pone.0073064
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the Id2 Gene Results in Altered Circadian Feeding Behavior, and Sex-Specific Enhancement of Insulin Sensitivity and Elevated Glucose Uptake in Skeletal Muscle and Brown Adipose Tissue

Abstract: Inhibitor of DNA binding 2 (ID2) is a helix-loop-helix transcriptional repressor rhythmically expressed in many adult tissues. Our earlier studies have demonstrated a role for ID2 in the input pathway, core clock function and output pathways of the mouse circadian system. We have also reported that Id2 null (Id2−/−) mice are lean with low gonadal white adipose tissue deposits and lower lipid content in the liver. These results coincided with altered or disrupted circadian expression profiles of liver genes inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(71 citation statements)
references
References 69 publications
8
61
0
2
Order By: Relevance
“…Only ~20% of mice escape from death but they are severely growth retarded (44, 50). These Id2 −/− mice displayed several metabolic phenotypes such as increased glucose tolerance, insulin sensitivity, reduced gonadal WAT, altered daily and circadian rhythms of feeding and locomotor activity, and increased energy expenditure (51). Although some of the observed metabolic phenotypes could be attributed to severe growth defects in Id2 −/− mice, it cannot be excluded that lack of Id2 could also have direct impact on adipose tissue metabolism.…”
Section: Id Proteinsmentioning
confidence: 99%
“…Only ~20% of mice escape from death but they are severely growth retarded (44, 50). These Id2 −/− mice displayed several metabolic phenotypes such as increased glucose tolerance, insulin sensitivity, reduced gonadal WAT, altered daily and circadian rhythms of feeding and locomotor activity, and increased energy expenditure (51). Although some of the observed metabolic phenotypes could be attributed to severe growth defects in Id2 −/− mice, it cannot be excluded that lack of Id2 could also have direct impact on adipose tissue metabolism.…”
Section: Id Proteinsmentioning
confidence: 99%
“…The generation and husbandry of Id2 −/− mice, and determination of genotypes, was performed as described previously [7,9]. Id2+/+ wild-type (WT) and Id2 −/− mice were on a mixed background for breeding purposes: 129sv/C57BL6J/FBVN [7,9].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, studies have shown that absence of Id2 results in impaired adipogenesis in vitro and that Id2 −/− mice have reduced gonadal white adipose tissue (WAT) and lipid content in the liver [3,4]. Our previous findings demonstrated that Id2−/− mice exhibit altered feeding and locomotor rhythms, sex- and age-dependent enhanced glucose tolerance and insulin sensitivity, and sex-dependent elevated glucose uptake in skeletal muscle and brown adipose tissue [9]. It is well known that risk, development and manifestation of obesity, metabolic syndrome and insulin-resistance are sexually dimorphic [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Aktywność tego centralnego zegara biologicznego regulowana jest przede wszystkim światłem. SCN poprzez wpływ na czynniki humoralne, autonomiczny układ nerwowy i termoregulację narzucają organizmowi "wystandaryzowany" czas lub, inaczej mówiąc, synchronizują molekularne zegary biologiczne w tkankach i komórkach obwodowych [23,24] w celu optymalizacji funkcji życiowych i dopasowania metabolizmu do zachowania organizmu: spożywania pokarmu, zwiększonej aktywności fizycznej, czuwania i snu [14]. Wpływają na produkcję melatoniny, ale także podlegają jej wpływo-wi, co stanowi jedno z wielu istotnych dla utrzymania cykliczności życia sprzężeń zwrotnych [17].…”
Section: Ośrodek Centralnyunclassified
“…Praca zmianowa i ograniczenie snu [14,24] prowadzą do spadku stężenia leptyny i zwiększonego apetytu [14,24]. Wśród osób wykonujących PZ po posiłku stężenie greliny (hormon łaknienia) obniża się mniej, a stężenie kseniny (hormonu sytości) mniej wzrasta w porównaniu z grupą kontrolną [14,34].…”
Section: Zaburzenia Hormonalneunclassified